The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fpls.2019.00551
|View full text |Cite
|
Sign up to set email alerts
|

Malus Hosts–Erwinia amylovora Interactions: Strain Pathogenicity and Resistance Mechanisms

Abstract: The bacterium, Erwinia amylovora , deposits effector proteins such as AvrRpt2 EA into hosts through the type III secretion pathogenicity island to cause fire blight in susceptible Malus genotypes. A single nucleotide polymorphism in the AvrRpt2 EA effector plays a key role in pathogen virulence on Malus hosts by exchanging one cysteine to serine in the effector protein sequence. Fire blight resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 59 publications
(87 reference statements)
1
44
0
Order By: Relevance
“…Selection for haplotype 6E in ‘Honeycrisp’-derived parents (e.g., ‘WA 38’) or selection against offspring with haplotype 6R might be valuable approaches to developing breeding populations with low susceptibility to fire blight. Although reduced susceptibility is not complete resistance, a successful combination of multiple reduced-susceptibility alleles from different sources will contribute to achieving more durable resistance 8 . In the long-term, breeders should focus on selecting against increased-susceptibility alleles and pyramiding resistance alleles at major genes derived from wild germplasm with reduced-susceptibility alleles to achieve durable resistance to fire blight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection for haplotype 6E in ‘Honeycrisp’-derived parents (e.g., ‘WA 38’) or selection against offspring with haplotype 6R might be valuable approaches to developing breeding populations with low susceptibility to fire blight. Although reduced susceptibility is not complete resistance, a successful combination of multiple reduced-susceptibility alleles from different sources will contribute to achieving more durable resistance 8 . In the long-term, breeders should focus on selecting against increased-susceptibility alleles and pyramiding resistance alleles at major genes derived from wild germplasm with reduced-susceptibility alleles to achieve durable resistance to fire blight.…”
Section: Discussionmentioning
confidence: 99%
“…Several quantitative trait loci (QTLs) additive and/or epistatic associated with resistance/susceptibility to fire blight have been detected throughout the apple genome 8 20 . Multiple QTLs have been mapped in wild Malus germplasm (e.g., ‘Evereste’, M. floribunda 821, M. robusta 5) characterized by astringent, crabapple-type fruit, with non-immediate breeding utility for apple scion improvement 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, susceptibility of a given apple variety also depends on the strain of E. amylovora [2224], as some have been identified that can overcome the fire blight resistance of a wild species, such as Mr5 [25, 26]. Vogt et al [27] proposed a gene-for-gene interaction in the host-pathogen system Mr5 – E. amylovora, whereby a single nucleotide polymorphism (SNP) in the avrRPT2 EA effector leading to a change from cysteine to serine determines the difference between a compatible and an incompatible interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This strain likely had higher co-evolutionary compatibility with the North American domesticated accessions in this study. The chances of host–pathogen compatibility are mainly determined by the profile of effector proteins in individual E. amylovora strains that are responsible for fire blight pathogenicity and triggering of the hypersensitive response in Malus 6 , 66 . However, the strains used in this study exhibit high genome similarity 49 and their considerably different phenotypic and genetic responses in host plants can lay out further investigations of Malus-Erwinia interactions.…”
Section: Discussionmentioning
confidence: 99%